1993
DOI: 10.1073/pnas.90.1.50
|View full text |Cite
|
Sign up to set email alerts
|

O2A progenitor cells transplanted into the neonatal rat brain develop into oligodendrocytes but not astrocytes.

Abstract: The differentiation of the bipotential 02Aprogenitor cell into an oligodendrocyte or a type 2 astrocyte has been well documented in cell cultures of various regions of the central nervous system. The appropriate tools to prove its existence in vivo have been lacking. We report on an in vitro-in vivo approach that combines stable labeling of an enriched population of cultured 02A progenitors by the fluorescent dye fast blue, followed by their transplantation into neonatal rat brains, which allowed us to study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(54 citation statements)
references
References 24 publications
2
51
0
Order By: Relevance
“…Cultured oligodendrocytes are capable of forming myelin-like sheets independent of neurons, although the interactions with neurons are still essential in producing proper myelin internodes. O-2A cells appear to generate myelinating oligodendrocytes but not type 2 astrocytes when cocultured in the presence of neurons (49). Thus, the induction of the enzymes involved in steroid biosynthesis in oligodendrocytes independent of neurons does not exclude the possibility that interactions between the two cells will change the pattern of expression.…”
Section: Discussionmentioning
confidence: 98%
“…Cultured oligodendrocytes are capable of forming myelin-like sheets independent of neurons, although the interactions with neurons are still essential in producing proper myelin internodes. O-2A cells appear to generate myelinating oligodendrocytes but not type 2 astrocytes when cocultured in the presence of neurons (49). Thus, the induction of the enzymes involved in steroid biosynthesis in oligodendrocytes independent of neurons does not exclude the possibility that interactions between the two cells will change the pattern of expression.…”
Section: Discussionmentioning
confidence: 98%
“…Transplanted OPCs have not been shown to generate astrocytes in the host CNS (Groves et al, 1993;Espinosa de los Monteros et al, 1993) except under pathological astrocyte-free conditions (Franklin et al, 1995). Based on these observations, the astrocytic fate of OPCs [O-2A progenitor cells (Raff et al, 1983)] has been generally discarded as an in vitro artifact.…”
Section: Ng2+cre+ Cells Generate Protoplasmic But Not Fibrous Astrocytesmentioning
confidence: 99%
“…It is well established that in culture, OPCs can give rise to both oligodendrocytes and type-2 astrocytes (Raff et al, 1983). The search for an astrocytic fate of NG2 glia in vivo has not yielded positive results because of the lack of evidence for the existence of cells that co-express NG2 and astrocytic markers and the lack of evidence that transplanted OPCs generate astrocytes in the CNS (Reynolds et al, 2002;Nishiyama et al, 2002;Nishiyama et al, 2005;Groves et al, 1993;Espinosa de los Monteros et al, 1993). Other studies, however, suggest that there may be glial progenitor cells that can give rise to both oligodendrocytes and astrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of cultures derived from dissociated rat optic nerve suggested that glial progenitor cells, the O2A cells, give rise to both type 2 astrocytes and oligodendrocytes (Raff et al, 1983a(Raff et al, , 1984Temple and Raff, 1985). However, two groups transplanted labeled O2A cells into the developing brain and found that only oligodendrocytes were produced, suggesting that there are distinct progenitors for astrocytes and oligodendrocytes (Espinosa de los Monteros et al, 1993;Groves et al, 1993). Subsequent studies in various systems led to the proposal that there are distinct domains for astrocyte and oligodendrocyte production, supporting the notion of distinct progenitors for the two glial types (Rowitch, 2004).…”
Section: Introductionmentioning
confidence: 99%